IFNα gene/cell therapy curbs colorectal cancer colonization of the liver by acting on the hepatic microenvironment - Mario Catarinella; Andrea Monestiroli; Giulia Escobar; Amleto Fiocchi; Ngoc Lan Tran; Roberto Aiolfi; Paolo Marra; Antonio Esposito; Federica Cipriani; Luca Aldrighetti; Matteo Iannacone; Luigi Naldini; et al. (EMBO Molecular Medicine)
Abstract Colorectal cancer (CRC) metastatic dissemination to the liver is one of the most life‐threatening malignancies in humans and represents the leading cause of CRC‐related mortality. Herein, we adopted a gene transfer strategy into mouse hematopoietic stem/progenitor cells to generate immune‐competent mice in which TEMs—a subset of Tie2+ monocytes/macrophages found at peritumoral sites—express interferon‐alpha (IFNα), a pleiotropic cytokine with anti‐tumor effects. Utilizing this strategy in mouse models of CRC liver metastasis, we show that TEMs accumulate in the proximity of hepatic metastatic areas and that TEM‐mediated delivery of IFNα inhibits tumor growth when administered prior to metastasis challenge as well as on established hepatic lesions, improving overall survival. Further analyses unveiled that local delivery of IFNα does not inhibit homing but limits the early phases of hepatic CRC cell expansion by acting on the radio‐resistant hepatic microenvironment. TEM‐mediated IFNα expression was not associated with systemic side effects, hematopoietic toxicity, or inability to respond to a virus challenge. Along with the notion that TEMs were detected in the proximity of CRC metastases in human livers, these results raise the possibility to employ similar gene/cell therapies as tumor site‐specific drug‐delivery strategies in patients with CRC.